2020
DOI: 10.1101/2020.03.22.20041004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 attack rate increases with city size

Abstract: The current outbreak of novel coronavirus disease 2019 (COVID-19) poses an unprecedented global health and economic threat to interconnected human societies. Until a vaccine is developed, strategies for controlling the outbreak rely on aggressive social distancing. These measures largely disconnect the social network fabric of human societies, especially in urban areas. Here, we estimate the growth rates and reproductive numbers of COVID-19 in US cities from March 14th through March 19th to reveal a power-law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 11 publications
12
130
1
7
Order By: Relevance
“…Moreover, note that the result in (A) appears to contrast with the results in Steir et al (5), who showed higher case growth rates with city size. The discrepancy can be explained by the different units employed in each study (case growth rate in (5) vs. fraction of total population infected at some point during a fixed time interval (this study)) and how ℛ was estimated in (5) (found to be city-size dependent) vs. assumed invariant in the present study. Case growth rate (number of new cases on day tnumber of new cases on day t-1 / number of new cases on day t-1) was found to increase with community size in the present study (not shown).…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…Moreover, note that the result in (A) appears to contrast with the results in Steir et al (5), who showed higher case growth rates with city size. The discrepancy can be explained by the different units employed in each study (case growth rate in (5) vs. fraction of total population infected at some point during a fixed time interval (this study)) and how ℛ was estimated in (5) (found to be city-size dependent) vs. assumed invariant in the present study. Case growth rate (number of new cases on day tnumber of new cases on day t-1 / number of new cases on day t-1) was found to increase with community size in the present study (not shown).…”
Section: Resultscontrasting
confidence: 83%
“…Although not explored here, numerical simulations for parameter values associated with points above the dashed line in (A) were influenced by 'herd immunity', i.e., when the proportion of the population in the susceptible class, S/N<(1.0-1.0/ℛ) (19). Moreover, note that the result in (A) appears to contrast with the results in Steir et al (5), who showed higher case growth rates with city size. The discrepancy can be explained by the different units employed in each study (case growth rate in (5) vs. fraction of total population infected at some point during a fixed time interval (this study)) and how ℛ was estimated in (5) (found to be city-size dependent) vs. assumed invariant in the present study.…”
Section: Resultsmentioning
confidence: 84%
“…To characterize the spread of COVID-19 in these areas, we assume an exponential growth of cases (valid for this novel virus during the time period we consider since no one yet had immunity) and characterize the growth exponent. In particular, following the method of [18], we subtract deaths from cases in each locality and find the slope of the log-log plot of cases as a function of time for each resulting time series of active COVID-19 cases. As noted there, estimating the growth rate of epidemics accurately is difficult, but we are only concerned with comparing growth rates among localities rather than obtaining precise growth exponent estimates.…”
Section: Methodsmentioning
confidence: 99%
“…We selected this variable as cities are more prone to early disease diffusion than rural areas due to higher concentration of interaction and movement in urban areas (42). COVID-19 has been preliminary found to diffuse faster in more populous urban areas in the United States (64). Settlement variable 2 is population density, defined as the population per square kilometre across a national territory.…”
Section: Datamentioning
confidence: 99%